On behavior of solutions of the quasilinear second-order parabolic equations in unbounded noncylindrical domains - Kurta, V. V. (Ukrains’kyi Matematychnyi Zhurnal, 1993)
The theorems of uniqueness of solutions are formulated in the classes of increasing functions for a mixed initial boundary value problem for the second-order degenerate quasiparabolic equations in unbounded noncylindrical domains. We presenta priori estimates of a special kind, analogous to the Saint-Venant principle. The proofs are based on the method of introducing a parameter.